About Gender Differences and the Social Environment in the Development of Entrepreneurial Intentions. (1st January 2016) - Santos, Francisco J.; Roomi, Muhammad Azam; Liñán, Francisco
Abstract : This study analyzes the interplay between gender differences and the social environment in the formation of entrepreneurial intentions. Data were obtained from two different European regions. The results show that the formation of entrepreneurial intentions is similar for men and women. At the same time, men consistently exhibit more favorable intentions than women do. Nevertheless, the perception of the social legitimation of entrepreneurship only serves to reinforce male entrepreneurial intentions, and not those of women. This holds for both regions and probably is a consequence of women feeling entrepreneurship to not be an acceptable career option for them. The implications of these results are discussed.